2018
DOI: 10.1002/jaba.521
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors that influence young children's food preferences and choices

Abstract: Researchers have identified an unbalanced diet as a key risk factor in the etiology of many chronic diseases (World Health Organization, ). Although researchers have found that numerous factors influence children's food choices, no assessment exists to identify these factors. In Experiment 1, we established preliminary empirical evidence of children's preferences for healthier and less‐healthy foods, and found that 16 of 21 children preferred less‐healthy foods to healthier foods. In Experiment 2, we establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
5
0
4
Order By: Relevance
“…Without a similar puppet, the conclusion that infants demonstrate a preference for similar others is speculative at best; infants’ preference or liking ought to be explicitly assessed. As several studies have demonstrated, it is not unreasonable to employ procedures in which infants sample the foods and a determination of their preference is based on observed behavior (e.g., Repacholi and Gopnik, 1997; Hamlin and Wynn, 2012; Ruffman et al, 2018; Zonneveld et al, 2018), rather than a single reach toward a potentially unfamiliar food.…”
Section: Discussionmentioning
confidence: 99%
“…Without a similar puppet, the conclusion that infants demonstrate a preference for similar others is speculative at best; infants’ preference or liking ought to be explicitly assessed. As several studies have demonstrated, it is not unreasonable to employ procedures in which infants sample the foods and a determination of their preference is based on observed behavior (e.g., Repacholi and Gopnik, 1997; Hamlin and Wynn, 2012; Ruffman et al, 2018; Zonneveld et al, 2018), rather than a single reach toward a potentially unfamiliar food.…”
Section: Discussionmentioning
confidence: 99%
“…Alan yazın incelendiğinde yiyecek içecek seçimini etkileyen faktörler yaş, cinsiyet, medeni hal, eğitim düzeyi ve gelir durumu gibi demografik faktörler (Zunft et al, 1997;Korkmaz, 2005;Ermiş vd., 2015;Gama et al, 2018;Saygı, 2018); fiziki görünüş, kilo ve hastalık durumu gibi genetik faktörler (Ermiş vd., 2015;Silventoinen ve Konttinen, 2020); aile, arkadaşlar, sosyal statü, dini inançlar gibi sosyo-kültürel faktörler (Oygard ve Klepp, 1996;Neumark-Sztainer et al, 1999;James, 2004;Voytyuk ve Hruschka, 2017;Keith et al, 2018); ekolojik ve çevresel faktörler (Bruening et al, 2012;González-Gil et al, 2019;Battaglia, 2020); açlık, karın doyurma, ruh hali, stres, alışkanlık, aşinalık, tercihler, duyusal faktörler ve kişisel güdüleme faktörleri gibi bireysel faktörler (Neumark-Sztainer et al, 1999;Swanson et al, 2013;Girgin ve Karakaş, 2017;Keith et al, 2018;Gama et al, 2018;González-Gil et al, 2019); besin değeri, tat, duyusal çekicilik, fiyat uygunluğu, maliyet, kalite, hijyen ve hazırlama kolaylığı gibi gıdaya ilişkin özellikler (Neumark-Sztainer et al, 1999;Korkmaz, 2005;Özdemir, 2010;Girgin ve Karakaş, 2017;Vilaro et al, 2017;Keith et al, 2018;Zonneveld et al, 2019); sağlık faktörü (Vilaro et al, 2017;Gama et al, 2018); fiziksel aktivite ihtiyacı (Neumark-Sztainer et al, 1999;Ermiş vd., 2015) ile sosyal medya ve reklamlar (Swanson et al, 2013;Vilaro et al, 2017) olarak sıralanabilir. Voytyuk ve Hruschka (2017: 126) bir insanın yeme standartlarının sosyo-kültürel yapıya bağlı olarak günlük yaşamda içselleştirildiğini ve bu nedenle, rutinleşmiş ve kökleşmiş olduğu için yiyecek se...…”
Section: Kuramsal çErçeveunclassified
“…İkinci kısımda ise öğrencilerin yiyecek seçimini etkileyen faktörlerin belirlenmesine yönelik 28 maddelik beşli Likert ölçeği yer almaktadır. Bu soruların oluşturulmasında alan yazındaki konu ile ilgili (Korkmaz, 2005;Yılmaz ve Özkan, 2007;Özdemir, 2010;Swanson et al, 2013;Girgin ve Karakaş, 2017;Işkın ve Sarıışık, 2017;Saygı, 2018;Keith et al, 2018;González-Gil et al, 2019;Zonneveld et al, 2019) çalışmalarından yararlanılmıştır.…”
Section: Yöntemunclassified
See 2 more Smart Citations